Uncertainty in continuous scatterplots, continuous parallel coordinates, and fibers - Zheng, Boyan; Sadlo, Filip (IEEE transactions on visualization and computer graphics, 2021)
In this paper, we introduce uncertainty to continuous scatterplots and continuous parallel coordinates. We derive respective models, validate them with sampling-based brute-force schemes, and present acceleration strategies for their computation. At the same time, we show that our approach lends itself as well for introducing uncertainty into the definition of fibers in bivariate data. Finally, we demonstrate the properties and the utility of our approach using specifically designed synthetic cases and simulated data.
Date of publication: 13 October 2020
Gesehen am 04.05.2021